(untitled) (Journal of the Bangladesh Agricultural University, 2025)
Agriculture remains a vital pillar of Bangladesh’s economy and rural livelihoods, employing nearly half of the workforce and contributing significantly to GDP, despite the nation’s shift toward industrial and service sectors. That’s why we are also attempting to shift from conventional practice to modern use of technology in order to cope with the situation. Because of this, it is essential to examines the adoption of modern and traditional agricultural methods in crop farming, livestock farming, and fish farming system. which will help us to identify the level of adoption, problems faced by farmers, and sustainable solutions that can increase agricultural productivity. Data from 219 farmers are collected through a quantitative survey and descriptive statistics are used for getting the result. The findings indicate that mechanization is gradually gaining ground, especially in using tractors, power tillers, and deep tubewells in crop cultivation. However, the traditional implements and practices still prevail because of the scarcity of modern technology, hands-on training, and high cost. In livestock, the situation improves a little as far as artificial insemination is concerned, though it still relies on conventional methods of feeding; fish farming has mainly adopted polyculture without following modern aquaculture technologies. The main constraints noted are financial, lack of availability of quality seeds and machinery, infestations, and lack of proper training. To support sustainable agriculture, it is important to offer targeted training programs, strengthen agricultural extension services, and improve farmers’ access to affordable credit, quality inputs, and subsidies for machinery and materials. Promoting climate-smart technologies is also essential. Overcoming existing challenges will require stronger government support and better infrastructure. J Bangladesh Agril Univ 23(2): 211-221, 2025